The experience of weight loss and its associated burden in patients with non‐small cell lung cancer: results of an online survey. Issue 2 (1st July 2017) - Rodriguez, Ana Maria; Braverman, Julia; Aggarwal, Dimple; Friend, John; Duus, Elizabeth
Abstract: Background: The main objectives of this study were to characterize and compare the burden of non‐small cell lung cancer (NSCLC) patients reporting considerable unintentional weight loss (≥ 5% in the past 6 months or ≥ 2% for a BMI < 20 kg/m 2 ) to those who did not. Methods: Ninety‐five advanced NSCLC patients were surveyed from the online patient‐powered community PatientsLikeMe, which included health‐related quality of life (QLQ‐C15‐PAL), anorexia‐cachexia symptoms/concerns (FAACT A/CS domain), distress levels, clinical/demographic characteristics, and impact of weight loss (open‐ended questions). Results: Thirty‐five patients (37%) had considerable weight loss at the time of the survey and 60 (63%) did not. Mean age was 59 years, and most were female (81%) and American (81%). Patients with weight loss reported significantly (p < 0.05) lower overall quality of life (55.2 vs. 66.9), worsened anorexia‐cachexia symptoms/concerns (30.7 vs. 36.0), and higher symptomology, specifically fatigue (64.8 vs. 49.1), nausea (19.5 vs. 9.2), and appetite loss (41.0 vs. 23.9) – than patients without weight loss. In addition, significantly more patients who lost weight reported moderate/high distress levels than patients who did not (71% vs. 38%). For patients with weight loss, changes in food taste, fatigue, and decrease in appetite were the most frequently reported symptoms with the greatest impact on their lives, and main worries included loss of energy and disease progression. Conclusions: Weight loss represents a substantial problem for NSCLC patients and symptoms associated with weight loss significantly impact patient lives. Interventions targeted at maintaining/increasing body weight may help to alleviate these findings.